Response type carbon sequestration cementing material for repairing ancient building cracks and preparation method of response type carbon sequestration cementing material
By using responsive carbon-solid gelling materials in the restoration of ancient buildings, the problems of low strength, poor environmental adaptability and insufficient weathering resistance in the early stage were solved, and high early strength, good environmental adaptability and strong deep cracks were achieved. Repair ability significantly improves repair effect and durability.
Patent Information
- Application Number
- CN202411672823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional lime mortar has problems in the early stages of low strength, poor environmental adaptability, weak resistance to rainwater erosion and weathering in the restoration of ancient buildings. Especially when deep cracks are repaired, the hardening reaction is slow, which affects the repair effect.
By using a responsive carbon-fixed gelling material, including lime, quartz sand, reaction precursor, response carrier, biochar, polyacrylamide, polypropylamide, polyvinyl alcohol and amino nanosilica, etc., the double polymerization is formed The synergy between matter networks and nanosilicon dioxide improves the carbon absorption capacity and carbon dioxide transmission capacity of the material, and improves early strength and environmental adaptability.
It has achieved high early strength, good environmental adaptability and strong deep crack repair capabilities. The material can be hardened quickly during the repair process, significantly improving the repair effect and durability.
Smart Images

Figure BDA0005146306800000041
Abstract
Description
Technical Field
[0001] The invention relates to a carbon-fixing cementitious material and a preparation method and application thereof, and in particular to a responsive carbon-fixing cementitious material for repairing cracks in ancient buildings and a preparation method thereof, and belongs to the technical field of building materials and ancient building repair. Background Art
[0002] At present, my country is continuously increasing its efforts to protect cultural relics and cultural heritage. The reasonable repair of ancient buildings has attracted great attention. During the repair project, the demand for advanced restoration technology and advanced restoration cementitious materials is increasing. In the construction of ancient masonry buildings, the cementitious materials mainly used were carbon-fixing cementitious materials such as lime mortar. Considering the compatibility of building materials, lime mortar is still the preferred choice in the process of ancient building restoration and partial reconstruction.
[0003] However, traditional lime mortar still has some weaknesses when used in modern renovation projects. The concentration of carbon dioxide in the air is low, and the hardening speed of traditional lime mortar is slow, resulting in low early strength. Traditional lime mortar has poor environmental adaptability. When encountering humid weather, its gelling ability becomes weak and it is not easy to construct. Traditional lime mortar has weak resistance to rain erosion and weathering, and it is easy to debond with the original ancient buildings. In addition, when used to repair deeper cracks, due to the limitation of the transmission performance of carbon dioxide within the material, the hardening reaction of the lime mortar deep inside the repaired crack will be slow, affecting the repair effect. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a responsive carbon-fixing cementitious material for repairing cracks in ancient buildings. The second purpose of the present invention is to provide a method for preparing the responsive carbon-fixing cementitious material for repairing cracks in ancient buildings.
[0005] Technical solution: The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings described in the present invention includes the following components by mass: 100-200 parts of lime, 200-500 parts of quartz sand, 4-12 parts of reaction precursor, 2-15 parts of response carrier, 1-5 parts of biochar, 0.01-0.08 parts of polyacrylamide A, 0.01-0.1 parts of polyacrylamide B, 0.5-2 parts of polyvinyl alcohol, 1-5 parts of amino nano-silica, and 50-200 parts of water.
[0006] Preferably, the lime is hydraulic lime, conforming to NHL2 of European standard EN459-1.
[0007] Preferably, the specific surface area of biochar is 500 to 1500 m 2 / g.
[0008] Preferably, the amino nano-silica is nano-silica modified with 3-aminopropyltriethoxysilane, and its particle size is 30 to 80 nm.
[0009] Preferably, polyacrylamide A is a polyacrylamide with a molecular weight of 10,000,000 to 1,5000,000.
[0010] Preferably, polyacrylamide B is polyacrylamide with a molecular weight of 3,000,000 to 5,000,000.
[0011] Preferably, the molecular weight of the polyvinyl alcohol is 50,000 to 100,000.
[0012] Preferably, the reaction precursor comprises the following components by weight: 5 to 12 parts of acrylamide, 1.5 to 3.3 parts of methylenebisacrylamide, 1.2 to 3.2 parts of polyethylene glycol, and 1.2 to 3.5 parts of tetramethylethylenediamine.
[0013] Preferably, the molecular weight of polyethylene glycol is 2,000-4,000.
[0014] Preferably, the response carrier comprises the following components by mass: 25-50 parts of APS solution, 15-30 parts of diatomaceous earth, 1-3 parts of nano titanium dioxide, 5-10 parts of solid paraffin, and 0.15-0.5 parts of ferrosoferric oxide powder.
[0015] Preferably, the preparation of the response carrier comprises the following steps:
[0016] (1) mixing diatomaceous earth and APS solution according to parts by mass, and subjecting the mixture to vacuum treatment so that APS is loaded into the diatomaceous earth to obtain APS-diatomaceous earth;
[0017] (2) According to the mass ratio, solid paraffin is heated, and ferroferric oxide powder, nano-titanium dioxide and APS-diatomaceous earth are added, and the mixture is fully stirred, rolled and shaped, and rapidly cooled to obtain a response carrier.
[0018] More preferably, in step (1), the APS solution is a 40 wt % ammonium persulfate solution.
[0019] More preferably, in step (1), the pressure is evacuated to -0.01 MPa and the treatment is performed for more than 12 hours.
[0020] More preferably, in step (2), the particle size of nano titanium dioxide is 30 to 100 nm.
[0021] More preferably, in step (2), the loose density of diatomaceous earth is 0.34 to 0.45 g / cm 3 .
[0022] More preferably, in step (2), the solid paraffin is heated to 55-75°C and rapidly cooled at 10°C.
[0023] The method for preparing the responsive carbon-fixing cementitious material for repairing cracks in ancient buildings of the present invention comprises the following steps:
[0024] (1) preparing a nano polymer solution: adding polyacrylamide A, polyacrylamide B, polyvinyl alcohol and nano silicon dioxide into water in sequence to obtain a nano polymer solution;
[0025] (2) Preparation of responsive carbon-fixing cementitious materials: The responsive carrier, nanopolymer solution, lime, quartz sand, reaction precursor and biochar are uniformly mixed to obtain a responsive carbon-fixing cementitious material.
[0026] Mechanism: The polyacrylamide, polyvinyl alcohol and nano-silica of the present invention can form a first type of polymer network inside the gelling material. The polymer molecular interface has a strong interaction with carbon dioxide, and cooperates with biochar to improve the carbon absorption capacity of the carbon-fixing gelling material and the ability to transmit carbon dioxide to the inside of the material. In addition, nano-silica can serve as an anchor to enhance the interaction between the polymer network and the inorganic components of the gelling material. The APS released by the response carrier in the later stage forms a second type of polymer network with the reaction precursor. Through slow release, early rapid polymerization is avoided, which causes poor working performance of the gelling material. In addition, the second polymer network has good moisture resistance, and the polymerization is not easily affected by external humidity, avoiding the influence of adverse weather environment. When the second type of polymer network reacts, it is an exothermic reaction. When repairing deeper cracks, the crack surface triggers the detachment of the response carrier encapsulation material through temperature, and the polymerization reaction is initiated. The heat after the reaction will continue to trigger the detachment of the internal response carrier encapsulation material, continue to release APS, and continue to react rapidly, so as to quickly provide strength for the gelling material deep in the crack.
[0027] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0028] (1) The responsive carbon-fixing cementitious material of the present invention has high early strength, good environmental adaptability, and strong deep crack repairing ability, and can harden quickly when repairing deep cracks.
[0029] (2) When the responsive carbon-fixing cementitious material of the present invention is used to repair cracks in ancient buildings, the dual polymer network has good adhesion and moisture resistance at the interface with the original ancient building materials, which effectively improves the durability of the repair material and has good application prospects in the field of ancient building restoration. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with embodiments.
[0031] Example 1
[0032] (1) Preparation of response carrier: 30 parts by mass of 40 wt% ammonium persulfate solution with a loose density of 0.4 g / cm 3 20 parts of diatomaceous earth, 1 part of nano titanium dioxide with a particle size of 30nm, 8 parts of solid paraffin, and 0.16 parts of ferrosoferric oxide powder.
[0033] (2) After mixing diatomaceous earth and ammonium persulfate solution, place the mixture in a vacuum container, evacuate to -0.01 MPa, and treat for 12 hours to load APS onto the diatomaceous earth to obtain APS-diatomaceous earth.
[0034] (3) The solid paraffin is heated to 70° C., and ferrosoferric oxide powder, nano-titanium dioxide and APS-diatomaceous earth are added thereto. The solid paraffin is fully stirred, rolled, and shaped, and then rapidly cooled at 10° C. to obtain a response carrier.
[0035] (4) Weighing the responsive carbon-fixing cementitious material: Weigh the following mass components: 150 parts of hydraulic lime (conforming to NHL2 of European standard EN459-1), 300 parts of quartz sand, 5 parts of reaction precursor, 5 parts of responsive carrier, and 1000 m 2 / g biochar 3 parts, molecular weight of 12,000,000 polyacrylamide A 0.03 parts, molecular weight of 3,500,000 polyacrylamide B 0.05 parts, molecular weight of 70,000 polyvinyl alcohol 0.8 parts, particle size of 50nm 3-aminopropyltriethoxysilane modified silica 3 parts, water 150 parts. Each reaction precursor includes 5 parts of acrylamide, 2 parts of methylenebisacrylamide, 2 parts of polyethylene glycol with a molecular weight of 3,000, and 1.2 parts of tetramethylethylenediamine.
[0036] (5) preparing a nanopolymer solution: adding polyacrylamide A, polyacrylamide B, polyvinyl alcohol and 3-aminopropyltriethoxysilane-modified silica to water in sequence to obtain a nanopolymer solution;
[0037] (6) Preparing a responsive carbon-fixing cementitious material: mixing a responsive carrier, a nanopolymer solution, lime, quartz sand, a reaction precursor, and biochar to obtain a responsive carbon-fixing cementitious material.
[0038] Example 2
[0039] (1) Preparation of response carrier: 35 parts of 40 wt% ammonium persulfate solution with a loose density of 0.4 g / cm 3 20 parts of diatomaceous earth, 2 parts of nano titanium dioxide with a particle size of 30nm, 6 parts of solid paraffin, and 0.2 parts of ferrosoferric oxide powder.
[0040] (2) After mixing diatomaceous earth and ammonium persulfate solution, place the mixture in a vacuum container, evacuate to -0.01 MPa, and treat for 12 hours to load APS onto the diatomaceous earth to obtain APS-diatomaceous earth.
[0041] (3) The solid paraffin is heated to 65° C., and ferrosoferric oxide powder, nano-titanium dioxide and APS-diatomaceous earth are added thereto. The solid paraffin is fully stirred, rolled, and shaped, and then rapidly cooled at 10° C. to obtain a response carrier.
[0042] (4) Weighing the responsive carbon-fixing cementitious material: Weigh the following mass components: 180 parts of hydraulic lime (conforming to NHL2 of European standard EN459-1), 400 parts of quartz sand, 6 parts of reaction precursor, 5 parts of responsive carrier, and a specific surface area of 1200 m 2 / g biochar 2 parts, molecular weight of 11,000,000 polyacrylamide A 0.01 parts, molecular weight of 4,000,000 polyacrylamide B 0.04 parts, molecular weight of 60,000 polyvinyl alcohol 1 part, particle size of 30nm 3-aminopropyltriethoxysilane modified silica 2 parts, water 160 parts. Each reaction precursor includes 8 parts of acrylamide, 3 parts of methylenebisacrylamide, 1.5 parts of polyethylene glycol with a molecular weight of 2,000, and 1.5 parts of tetramethylethylenediamine.
[0043] (5) preparing a nanopolymer solution: adding polyacrylamide A, polyacrylamide B, polyvinyl alcohol and 3-aminopropyltriethoxysilane-modified silica to water in sequence to obtain a nanopolymer solution;
[0044] (6) Preparing a responsive carbon-fixing cementitious material: mixing a responsive carrier, a nanopolymer solution, lime, quartz sand, a reaction precursor, and biochar to obtain a responsive carbon-fixing cementitious material.
[0045] Comparative Example 1
[0046] The difference between this comparative example 1 and embodiment 1 is that the components of this comparative example only include lime, quartz sand and water, which are mixed evenly.
[0047] In accordance with the requirements of GB / T25181-2019 "Premixed Mortar" and JGJ / T70-2009 "Standard for Test Methods for Basic Performance of Building Mortar", the cementitious materials prepared in the examples and comparative examples were molded and performance tested. For Example 1 and Example 2, 1 hour after the specimen was molded, a 300W infrared lamp was used to irradiate the surface of the specimen for 60 seconds to control the release of reactants in the response carrier. The durability of the samples was tested by an acid resistance test. The specimens after 28 days of curing were soaked in an 8% concentration of acetic acid solution, and the ratio of the remaining volume of the specimen to the original volume after 6 hours was observed. The test results are shown in Table 1.
[0048] Table 1 Performance data of cementitious materials prepared in Examples and Comparative Examples
[0049]
[0050] It can be seen from the data in Table 1 that the responsive carbon-fixing cementitious materials prepared in Examples 1 to 2 have significantly improved 1d strength, 28d strength and bonding strength compared with Comparative Example 1, and have better durability.
[0051] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A responsive carbon-fixing cementitious material for repairing cracks in ancient buildings, characterized in that: It includes the following components by mass: 100-200 parts of lime, 200-500 parts of quartz sand, 4-12 parts of reaction precursor, 2-15 parts of response carrier, 1-5 parts of biochar, 0.01-0.08 parts of polyacrylamide A, 0.01-0.1 parts of polyacrylamide B, 0.5-2 parts of polyvinyl alcohol, 1-5 parts of amino nano-silica, and 50-200 parts of water.
2. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 1, characterized in that: The lime is hydraulic lime, which meets the NHL2 of European standard EN459-1; the specific surface area of biochar is 500~1500m 2 / g.
3. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 1, characterized in that: Polyacrylamide A is a polyacrylamide with a molecular weight of 10,000,000 to 15,000,000; polyacrylamide B is a polyacrylamide with a molecular weight of 3,000,000 to 5,000,000.
4. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 1, characterized in that: The amino nano-silica is nano-silica modified by 3-aminopropyltriethoxysilane, the particle size of which is 30-80 nm, and the molecular weight of the polyvinyl alcohol is 50,000-100,000.
5. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 1, characterized in that: The reaction precursor comprises the following components by weight: 5 to 12 parts of acrylamide, 1.5 to 3.3 parts of methylenebisacrylamide, 1.2 to 3.2 parts of polyethylene glycol, and 1.2 to 3.5 parts of tetramethylethylenediamine; the molecular weight of the polyethylene glycol is 2,000 to 4,000.
6. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 1, characterized in that: The response carrier comprises the following components by weight: 25-50 parts of APS solution, 15-30 parts of diatomaceous earth, 1-3 parts of nano titanium dioxide, 5-10 parts of solid paraffin and 0.15-0.5 parts of ferrosoferric oxide powder.
7. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 6, characterized in that: The preparation of the response carrier includes the following steps: (1) mixing diatomaceous earth and APS solution according to parts by mass, and subjecting the mixture to vacuum treatment so that APS is loaded into the diatomaceous earth to obtain APS-diatomaceous earth; (2) According to the mass ratio, solid paraffin is heated, and ferroferric oxide powder, nano-titanium dioxide and APS-diatomaceous earth are added, and the mixture is fully stirred, rolled and shaped, and rapidly cooled to obtain a response carrier.
8. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 7, characterized in that: In step (1), the APS solution is a 40 wt % ammonium persulfate solution, which is evacuated to -0.01 MPa and treated for more than 12 hours.
9. The responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to claim 7, characterized in that: In step (2), the particle size of nano titanium dioxide is 30nm to 100nm, and the loose density of diatomaceous earth is 0.34 to 0.45g / cm 3 , heat the solid paraffin to 55-75°C and quickly cool it at 10°C.
10. The method for preparing the responsive carbon-fixing cementitious material for repairing cracks in ancient buildings according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) preparing a nano polymer solution: adding polyacrylamide A, polyacrylamide B, polyvinyl alcohol and nano silicon dioxide into water in sequence to obtain a nano polymer solution; (2) Preparation of responsive carbon-fixing cementitious materials: The responsive carrier, nanopolymer solution, lime, quartz sand, reaction precursor and biochar are uniformly mixed to obtain a responsive carbon-fixing cementitious material.